KAJIAN PEMANTAUAN PERUBAHAN PENUTUPAN LAHAN BERBASIS PENGINDERAAN JAUH DI KOTAWARINGIN BARAT - Beni Iskandar; Nanang Hanafi; Rifqi Anshari (Jurnal Belantara, 2022)
The first step in monitoring deforestation is to measure and identify land cover changes. Our research uses remote sensing technology, because it has advantages such as: cheap, transparent, fast and has measurable accuracy and temporal analysis. This study aims to identify, measure, and analyze trends in land cover change in 1990-2000, 2000-2012, and 2012-2021. The results showed that there were 18 land cover classes with details of 3 forest classes; and 15 non-forest classes; Forest class decreased throughout 1990 to 2021, the trend of changing forest cover was deforestation into plantations, swamp shrubs, dryland agriculture mixed with shrubs, and swamps. The rate of deforestation in 1990-2000 was 3.07%, deforestation in 2000-2012 was 3.02%, and deforestation in 2012-2021 was 1.02%. The accuracy of land cover classification is 91%.